Hepatoprotective effect of 7-Hydroxycoumarin against Methyl glyoxal toxicity via activation of Nrf2. (1st October 2017) - Li, Dan; Wang, Na; Zhang, Jingdong; Ma, Shuren; Zhao, Zhuangzhuang; Ellis, Elizabeth M.
Abstract: Methyl glyoxal (MG), a major precursor of advanced glycation end-products, has been identified as significant in the progression of several diseases including aging, diabetes and neurodegenerative diseases as well as causing hepatic damages. 7-hydroxycoumarin (7-HC), a natural-occurring derivative of coumarin from fruits and plants, has been reported to exert antioxidant and free radical-scavenging properties, protecting cells from aldehydes and oxidants. In this study, the ability of 7-HC to protect human HepG2 cells against MG-induced toxicity and oxidative stress was investigated. Results show that 7-HC pretreatment significantly attenuates MG-induced cytotoxicity, apoptotic changes and ROS accumulation and that this protection is shown to be associated with the induction of the nuclear factor erythroid 2-related factor 2 (NRF2) and its downstream detoxifying enzymes. In response to 7-HC, NRF2 protein translocates from cytosol to the nuclei. In addition, depletion of NRF2 by siRNA significantly reduces the protective effect of 7-HC against MG, suggesting that NRF2 plays an important role in the protective function of 7-HC. These findings highlight the potential for the interventional activation of the NRF2 induction via the non-toxic natural phytochemical 7-HC as a novel therapeutic approach towards the detoxification of MG, with the aim of halting the progression of diseases in which MG has been implicated. Highlights: 7-hydroxycoumarin treatment protects against methyl glyoxal -induced cytotoxicity, apoptosis and ROS accumulation. AKR7A2, AKR1C3 and AKR7A3 enzymes are inducible by 7-hydroxycoumarin. 7-hydroxycoumarin increases NRF2 nuclear accumulation. NRF2 contributes significantly to the protective effect of 7-HC treatment.